IMPLEMENTASI PENCATATAN AKTIVITAS MAHASISWA MENGGUNAKAN WEB SERVICE PADA FEEDER PDDIKTI DENGAN METODE EXTREME PROGRAMMING - Pranatawijaya, Viktor Handrianus (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2020)
One of the features in the Feeder PDDIKTI application is the student activity feature. The feature is used to record student activities with participants' activities, supervisors and examiners. The problem with the Feeder PDDIKTI application when recording student activities is that the operator must input data one by one to the application. Therefore DIKTI also provides web services that can be used so that the recording process can be better.Implementation of recording student activities using web services on the Feeder PDDIKTI with extreme programming methods is carried out in accordance with the stages. In the planning part, an analysis is carried out on the business needs and user stories, in the design, use case diagrams and activity diagrams are made, coding is done by implementing the design using the PHP programming language, and testing is done using black box testing.In running the application, upload excel files are used for student activity data, activity participants, supervisors and examiners. After the student activity is successfully uploaded an excel file is generated from the system which contains student activities that already have the id_akt_mhs attribute. These attributes will be used to link student activity data with activity participants, supervisors, and examiners when filling in data in an excel file. Applications made are not yet connected to the Academic Information System Application so that for future development it is expected to be able to connect and retrieve data directly from the Academic Information System Application.